2020
DOI: 10.1021/acscatal.0c01121
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Metal–Support Interaction and Enhancing the Stability of Titania-Supported Cobalt Fischer–Tropsch Catalysts via Carbon Nitride Coating

Abstract: Supported metal catalysts have found numerous applications in many catalytic reactions, including Fischer-Tropsch synthesis. Metal dispersion, metal reducibility, catalytic performance and catalyst stability are usually strongly affected by the interaction of active phase and support. A strong metal support interaction has been previously reported for titania supported catalysts.In this work, a series of titania supported cobalt catalysts promoted via deposition of a layer of carbon nitride were prepared, char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…This, not only improved catalysts activity, but also increased catalyst resistance to deactivation. In a recent study, Hong et al [153] improved the reducibility and stability of Co/TiO2 catalyst by tuning MSI via carbon nitride coating. In addition, the presence of a carbon nitride layer on the TiO2 surface inhibited the encapsulation of Co 0 particle by the TiO2 support during FTS [153].…”
Section: Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This, not only improved catalysts activity, but also increased catalyst resistance to deactivation. In a recent study, Hong et al [153] improved the reducibility and stability of Co/TiO2 catalyst by tuning MSI via carbon nitride coating. In addition, the presence of a carbon nitride layer on the TiO2 surface inhibited the encapsulation of Co 0 particle by the TiO2 support during FTS [153].…”
Section: Deactivationmentioning
confidence: 99%
“…In a recent study, Hong et al [153] improved the reducibility and stability of Co/TiO2 catalyst by tuning MSI via carbon nitride coating. In addition, the presence of a carbon nitride layer on the TiO2 surface inhibited the encapsulation of Co 0 particle by the TiO2 support during FTS [153]. The impact of catalyst pretreatment on deactivation in FTS was also evaluated by Aluha et al [79] using plasma synthesized Co/C catalysts.…”
Section: Deactivationmentioning
confidence: 99%
“…14 In the most basic sense, when CoNPs interact weakly with the support surface, migration occurs, leading to aggregation and a lowering of the cobalt dispersion and apparent reaction activity as the number of surface active sites decreases. 15,16 Alternatively when the interaction between CoNPs and the support is intimate or strong they have been observed to become encapsulated by a TiO x (x < 2) overlayer ($few atomic layers thick) particularly aer reduction. 9,[16][17][18] The encapsulation by TiO x actually was also reported in other TiO 2 supported metal NPs such as Au, Pt and Rh.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Alternatively when the interaction between CoNPs and the support is intimate or strong they have been observed to become encapsulated by a TiO x (x < 2) overlayer ($few atomic layers thick) particularly aer reduction. 9,[16][17][18] The encapsulation by TiO x actually was also reported in other TiO 2 supported metal NPs such as Au, Pt and Rh. [19][20][21][22] Interestingly it has been reported that the amorphous TiO x suboxide layer around CoNPs can be tuned and broken by sequential treatments in reducing/oxidising gases, resulting in signicantly improved catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, varying Co species exist in the impregnation solution, which makes the drying and calcination process less controllable and results in the inhomogeneous Co oxide particles over the support due to the different thermal decomposition behavior and the interaction with the support of the Co species. Although the obtained catalysts have a higher catalytic activity, they usually exhibit a high deactivation rate due to the inhomogeneous Co particle size distributions, which leads to the sintering of small cobalt particles through Ostwald ripening [23][24][25][26][27]. Therefore, exploring controllable methods for the synthesis of highly dispersed Co-supported catalyst with homogenous size distribution of Co is crucial for development of high-performance FT catalysts in industry.…”
Section: Introductionmentioning
confidence: 99%